2006
DOI: 10.2351/1.2227020
|View full text |Cite
|
Sign up to set email alerts
|

Microstructuring using femtosecond pulsed laser ablation

Abstract: Hopes are high that such structures can be utilized in a mold to generate a rough surface that amplifies the hydrophobic properties of the material used in the replication process. The presented experiments are first steps towards a deeper understanding of the emergence of microstructures, the possible variations and the reproducibility thereof. The ripple structure is discussed for about 30 years, and the proposed models do not predict all experimental results. This research gives new experimental data on whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…For all cases, the periodicity increased with increasing fluence [104]. In contrast, the effect of fluence on LIPSS spacing at normal incidence was not detected on SS304 by Groenendijik et al [71]. Thus, the authors suggested that fluence does not directly relate to the LIPSS spacing.…”
Section: Periodic Nanostructuresmentioning
confidence: 43%
See 4 more Smart Citations
“…For all cases, the periodicity increased with increasing fluence [104]. In contrast, the effect of fluence on LIPSS spacing at normal incidence was not detected on SS304 by Groenendijik et al [71]. Thus, the authors suggested that fluence does not directly relate to the LIPSS spacing.…”
Section: Periodic Nanostructuresmentioning
confidence: 43%
“…Chaotic and rugged structures were observed on Ti, SS304, SS316, and Cu [71,81]. It was observed that high fluences and high line overlap favour rugged-chaotic structures.…”
Section: Formation Of Lipss and Nanowhiskers On Top Of Columnar Strucmentioning
confidence: 78%
See 3 more Smart Citations